p-13=31

Simple and best practice solution for p-13=31 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for p-13=31 equation:


Simplifying
p + -13 = 31

Reorder the terms:
-13 + p = 31

Solving
-13 + p = 31

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '13' to each side of the equation.
-13 + 13 + p = 31 + 13

Combine like terms: -13 + 13 = 0
0 + p = 31 + 13
p = 31 + 13

Combine like terms: 31 + 13 = 44
p = 44

Simplifying
p = 44

See similar equations:

| a(x)+b=c | | 7e-4(6+2w)=3(w-8) | | -4(5x-7)+1=20x+29 | | 25x+20=78 | | 47x=46x+1 | | 60+4n=76 | | 40x+18=86 | | 3(x+2)-8x=4x+1 | | 20x-10=110 | | 30x-18=150 | | 12=v+2 | | (4+4i)+(-5+7i)-8i= | | 8(-3b+6)=96 | | 1.3n-.03=9 | | 4xy^2/y | | 20×1/4 | | x^2-40=41 | | 3(2l+10)=48 | | y+x=10-4 | | 3x+22=x+4 | | 0.6(x-1)+0.2x=6.6 | | y=-2.1x+3.4 | | -x-19=2x+8 | | 49=-7z | | y=2x^2-36x+c | | -2(x+2)+3=3(x+3)+4 | | (x-2)(x-2)+(y-6)(y-6)=25 | | 2+f=-3 | | x-6+x=78 | | -y/4=-16 | | 2x=960 | | x^3+4=13 |

Equations solver categories